Familial Idiopathic Intracranial Hypertension in Two Non-obese Chinese Sisters - Qiao, Lei; Wei, Yanping (Frontiers in Neurology, 2020)
Background: Familial idiopathic intracranial hypertension (FIIH) is a rare condition, the etiology of which is unclear. Aims: To describe two non-obese Chinese sisters who met the criteria of FIIH and to analyze the clinical features and prognosis of FIIH. Methods: The clinical course, treatment, and prognosis of these two patients were analyzed retrospectively. Meanwhile, all the literature of familial IIH (FIIH) was reviewed. Results: These two sisters presented with headaches and visual impairment in their mid-thirties. Magnetic resonance imaging (MRI) of the brain was unremarkable except for partial empty sella. No comorbidities or defined causes were detected. Headaches were partially relieved by dehydrated medicine, whereas the visual impairment persisted. Conclusion: In cases where patients present with headaches, empty sella are found on an MRI, and there is visual impairment with or without papilla edema, intracranial hypertension should be excluded. Furthermore, we should pay more attention to the relatives of those patients with increased intracranial hypertension.